Determination of Antimony in Environmental Water by Primary-Secondary Wavelengths New Spectrophotometry - Gao, Hong-Wen; Zhang, Peng-Fei (Asian Journal of Chemistry, 2010)
An acidic solution of antimony (Sb) may react with malachite green to from a blue coloured compound that can be extracted by benzene. In this paper with the absorption property of a suspended particle liquid against light, new analytical method as primary-secondary wavelengths spectrophotometry (P.S.W.S.) was studied to determine trace amounts of Sb in environmental water sample. It is recommended in both precision and sensitivity than the traditional single colorimetry method. Experiments for practical water samples have shown that the detection limit was 0.002 μg/mL Sb, the relative standard deviation is less than 8% and the recovery rate varies between 92.3 to 105%.